GAMBARAN PREFERENSI PEMILIHAN PASANGAN HIDUP PADA MAHASISWA UNIVERSITI KEBANGSAAN MALAYSIA - Puteri Amylia Binti Ulul Azmi; Suzana Mohd Hoesni (UIR Press, 2019)
This study aims to determine the description of preference for life partner selection at students of Universiti Kebangsaan Malaysia (UKM). This research is descriptive quantitative research. A total of 160 UKM students were the subjects in this study which were determined by a purposive sampling technique. The instruments used in this study were 13 items Mate Preferences Questionnaire and 4 items questionnaire pairs characteristics. Based on the results of the descriptive statistical analysis shows that the choice of pair preference most students choose is the preference of religiosity of couples with a mean rank value of mean = 2.6813 and the lowest is the preference of pair selection based on the creativity of couples with a mean rank value of mean = 10.7125. The results of statistical analysis of the 4 item pairs questionnaire characteristics showed that male students were more likely to choose a partner who was younger and who had a physical attraction, while female students were more likely to choose an older partner and had good financial prospects. Students who are Muslim prefer religious partners compared to non-Muslim students. Keywords : Love, Intimacy, Mate References Abstrak Penelitian ini bertujuan untuk mengetahui gambaran preferensi pemilihan pasangan hidup pada mahasiswa Universiti Kebangsaan Malaysia (UKM). Penelitian ini merupakan penelitian kuantitatif deskriptif. Sejumlah 160 orang mahasiswa UKM menjadi subjek dalam penelitian ini yang ditentukan dengan teknik purposive sampling. Instrumen yang digunakan dalam penelitian ini adalah 13 aitem Mate Preferences Questionnaire dan 4 aitem angket karakteristik pasangan. Berdasarkan hasil analisis statistik deskriptif menunjukkan bahwa preferensi pemilihan pasangan yang paling banyak dipilih mahasiswa adalah preferensi religiusitas pasangan dengan nilai mean rank sebesar 2,6813 dan yang paling rendah adalah preferensi pemilihan pasangan berdasarkan kreativitas pasangan dengan nilai mean rank sebesar 10,7125. Hasil analisis statistik dari 4 aitem angket karakteristik pasangan diperoleh hasil bahwa mahasiswa laki-laki lebih cenderung untuk memilih pasangan yang lebih muda dan yang memiliki daya tarik fisik, sedangkan mahasiswa perempuan lebih cenderung memilih pasangan yang lebih tua dan memiliki prospek keuangan yang baik. Mahasiswa yang beragama islam lebih memilih pasangan yang seagama dibandingkan dengan mahasiswa non-muslim. Kata kunci : Cinta, Keintiman, Pemilihan Pasangan Hidup